Akwinata o definicji sakramentu. "Scriptum super Sententiis", IV, d. 1, q. 1, a. 1. Wprowadzenie i przekład - Przanowski, Mateusz (Przegląd Tomistyczny, 2025)
Aquinas on the Definition of the Sacrament in "Scriptum super Sententiis", IV, d. 1, q. 1, a. 1. Introduction and Translation The excerpt from the "Scriptum super Sententiis" is a crucial element in the development of St. Thomas Aquinas’ sacramentology. In this passage, Aquinas addresses the definition of a sacrament of the New Law. In doing so, he analyzes the most important definitions of the sacrament available at the time, not only those presented by Peter Lombard but also later ones. This fragment of the "Scriptum" is therefore significant for determining the fundamental components of the theology of the sacrament and may also help clarify key terminological and conceptual issues. By studying this text, we have the opportunity to access Aquinas’ earliest reflection on the foundations of sacramentology, which will later serve as the starting point for the formulation of more mature interpretations.